Development of a climbing robot for grit blasting operations in shipyards - Faina, A.; Souto, D.; Deibe, A.; Lopez-Pena, F.; Duro, R.J.; Fernandez, X. (2009 IEEE International Conference on Robotics and Automation, 2009)
This paper deals with the design and construction of a climbing robot for performing grit blasting operations in shipyards. The robot is based on a double sliding platform that uses permanent magnets for attachment. It is lightweight and compact and can move up and along the shipside with any inclination while grit blasting the surface to pre-specified surface quality levels. It can also rotate to compensate for hull curvature and to avoid obstacles while performing its task. The blasting operation is modulated by a vision based quality control system that is used by the mission control system to adapt the blasting parameters in order to attain the desired quality levels while maximizing the surface area the robot strips per unit time.